Land and Soil - Global Environment Outlook (GEO-6): Healthy Planet, Healthy People Chapter 8 - United Nations Environment Programme (2019)
The main messages of the fth report of the Global Environment Outlook (GEO-5) could be extrapolated to GEO-6. Perhaps the most important difference is the recognition of climate change as a driver of environmental change, and how it has the potential for altering land resources on its own (see Chapter 2). Climate change usually exacerbates ecosystem degradation and a more variable climate degrades ecosystems more strongly. Another difference is the increasing recognition of the critical function that clear property rights play for land-resource stewardship and the crucial role of rural inhabitants in land conservation.